2020
DOI: 10.1101/2020.03.02.20030189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibody responses to SARS-CoV-2 in patients of novel coronavirus disease 2019

Abstract: BackgroundThe novel coronavirus SARS-CoV-2 is a newly emerging virus. The antibody response in infected patient remains largely unknown, and the clinical values of antibody testing have not been fully demonstrated. MethodsA total of 173 patients with confirmed SARS-CoV-2 infection were enrolled. Their serial plasma samples (n = 535) collected during the hospitalization period were tested for total antibodies (Ab), IgM and IgG against SARS-CoV-2 using immunoassays. The dynamics of antibodies with the progress a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

74
860
6
35

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 728 publications
(982 citation statements)
references
References 11 publications
74
860
6
35
Order By: Relevance
“…The results of our study indicated that convalescent patients had a higher antibody level than inpatients, which highlight the positive correlation between recovery and days since onset (Spearman correlation coefficient=0.5426, P<0.0001). Besides, we also found that antibody levels in asymptomatic or mild patients were slightly lower than moderate or severe patients, which was in line with other previous studies [16][17] . Zhang [17] came to a similar conclusion that severe cases were more frequently found in COVID-19 patients with high IgG levels, compared to those who with low IgG levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of our study indicated that convalescent patients had a higher antibody level than inpatients, which highlight the positive correlation between recovery and days since onset (Spearman correlation coefficient=0.5426, P<0.0001). Besides, we also found that antibody levels in asymptomatic or mild patients were slightly lower than moderate or severe patients, which was in line with other previous studies [16][17] . Zhang [17] came to a similar conclusion that severe cases were more frequently found in COVID-19 patients with high IgG levels, compared to those who with low IgG levels.…”
Section: Discussionsupporting
confidence: 93%
“…The effect of gender was also not statistically significant in both univariate (P=0.9426) and multivariate (P=0.8543) GEE analysis. A significant neutralizing antibody response was observed in older patients with a geometric mean titer of 1:220.1 (95% CI, 71.8 to 674.8) compared to patients at age of [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] (1:71.0, 95% CI, 27.7 to 181.8) and at age of 31-60 (1:200.6, 95% CI, 150.4 to 267.6) (P=0.0140).…”
Section: Changes On Antibody Levels With Clinical Classificationmentioning
confidence: 95%
“…Zhao et al [19] reported that the overall RNA positive rate was lower than 70% in patients on the first week post symptoms onset and fall to 50% on the next week.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, 23/112 patients in G2 had crackling sounds heard on pulmonary auscultation, and it is probable that some of them may have presented CT scan findings enabling us to validate a diagnosis of COVID-19. In recent studies, combination of RT-PCR (on respiratory samples) and serological tests also seems to enhance the sensitivity for COVID biological diagnosis [13].…”
Section: Discussionmentioning
confidence: 99%